2017
DOI: 10.1002/lno.10553
|View full text |Cite
|
Sign up to set email alerts
|

Trophic discrimination of stable isotopes and potential food source partitioning by leaf‐eating crabs in mangrove environments

Abstract: Diet composition of leaf-eating mangrove crabs is a puzzle among mangrove ecologists. Nutrient-poor leaf litter can in most cases not support animal growth. Food partitioning (mangrove leaves, animal tissue, and microphytobenthos [MPB]) of sesarmid and ucidid mangrove crabs from eight locations in four countries was assessed using the concentration-dependent stable isotope mixing model, IsoConc. While stable C and N isotopes have the potential to track the origin and proportion of food sources for these crabs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 62 publications
7
33
0
Order By: Relevance
“…Several studies have demonstrated that sesarmid crabs mainly utilize plant material with sediment as nutrient sources, especially in mangrove ecosystems (Lee 1998;Kristensen et al 2017). Our results support those of previous studies showing that large sesarmid crabs exploit plant materials more compared to the small individuals in a feeding experiment and a mangrove ecosystem (Emmerson and McGwynne 1992;Pahlas 2013).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Several studies have demonstrated that sesarmid crabs mainly utilize plant material with sediment as nutrient sources, especially in mangrove ecosystems (Lee 1998;Kristensen et al 2017). Our results support those of previous studies showing that large sesarmid crabs exploit plant materials more compared to the small individuals in a feeding experiment and a mangrove ecosystem (Emmerson and McGwynne 1992;Pahlas 2013).…”
Section: Discussionsupporting
confidence: 91%
“…For running the model, δ 13 C and δ 15 N values of the crabs and diets, such as plant material and sediment, collected in both May and September were used. The stable signatures of MPB, assumed as one of diets applied, were from the global averages (δ 13 C: − 20.2‰ ± 2.1‰ and δ 15 N: 2.4‰ ± 1.2‰) compiled from various habitats (Kristensen et al 2017) because of incomplete sampling in this study. The discrimination factors of the diets were referred to the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations